Towards a Unified Macroscopic Description of Exciton Diffusion in Organic Semiconductors (Communications in Computational Physics, 2018)
We study the exciton diffusion in organic semiconductors from a macroscopicviewpoint. In a unified way, we conduct the equivalence analysis betweenMonte-Carlo method and diffusion equation model for photoluminescence quenchingand photocurrent spectrum measurements, in both the presence and the absenceof Förster energy transfer effect. Connections of these two models to Stern-Volmermethod and exciton-exciton annihilation method are also specified for the photoluminescencequenching measurement.